5 Fluorouracil‐loaded biosynthesised gold nanoparticles for the in vitro treatment of human pancreatic cancer cell - Senthil Kumar Chinnaiyan; Agnes Mary Soloman; Ramesh Kannan Perumal; Arun Gopinath; Madhan Balaraman (IET Nanobiotechnology)
In this study, green synthesis of gold nanoparticles (AuNPs) was performed by a sunlight irradiation method using the Borassus flabellifer fruit extract as a reducing agent. 5‐Fluorouracil (5‐FU)‐loaded GG capped AuNPs (5FU‐G‐AuNPs) was prepared. The nanoparticles was further characterised by UV‐visible spectra, particle size analysis, zeta potential, SAED, HRTEM, and XRD. The MTT assay results showed the suitability 5‐FU‐G‐AuNPs. In this study, 5‐FU‐G‐AuNPs exhibited potential cytotoxic and apoptotic effects on (MiaPaCa‐2) cell line.